The Analysis of Factors Causing Stress and Burnout in Expatriates: Case Study at PT. XYZ - Anindea Pudjie Hapsari; Didin Hikmah Perkasa (DEAL: International Journal of Economics and Business, 2024)
Nowadays, many manufacturing companies have started sending their employees abroad as expatriates to manage international operations, expand markets, and integrate their global operations. Working in a foreign country often poses challenges that can lead to stress and burnout. Stress and burnout can have a negative impact on work performance, so it is important for companies to understand and manage the factors that cause them. This study aims to determine the factors that cause stress and burnout in expatriates at PT XYZ. This research is a qualitative research. The data collection methods used are interviews, documentation and thematic analysis, using 11 expatriate informants who work at PT XYZ. The results showed that high workload, lack of job control, social isolation, environmental uncertainty, and language difficulties were the main factors affecting stress and burnout levels, but they and the management of PT XYZ tried to overcome them. The purpose of this study is to provide an in-depth understanding of expatriates' subjective experiences and suggest practical solutions to manage their stress and burnout conditions. This research is expected to provide guidance for manufacturing companies in improving the well-being and performance of their expatriates.